Chegando em Springfield: Um estudo crítico sobre a série Os Simpsons - Chantal Herskovic (2005)
This essay analyses the animated series The Simpsons as a cartoon sitcom, for both mature and young audience. The show The Simpsons was chosen because it is the longest prime-time comedy show on television, and has instigated the return of prime-time animation to television. Through The Simpsons, shape, creation, production its studied and the way the content in the episodes are well developed, reaching discussion points of view and debating issues about contemporary society throughout the satire and irony, exploiting the many possibilities of the series narrative structure. It is considered the most critical TV show nowadays. This essay delineates a development overview of the series showing the context, which the cartoon content develops by the analysis of episodes. It also creates meta-texts to make critics about the popular culture and the own animated series. It also makes several references to movies and other works, creating a new and original production. A study about this animated series is indispensable to a country, as Brazil, in which this industry sector points new ways for its development in the 21st century and its reaching its own space on the TV, whatever nationally or internationally broadcasted, like The Simpsons conquered on 1989.